Femtosecond Field‐Driven On‐Chip Unidirectional Electronic Currents in Nonadiabatic Tunneling Regime. Issue 8 (16th June 2021) - Shi, Liping; Babushkin, Ihar; Husakou, Anton; Melchert, Oliver; Frank, Bettina; Yi, Juemin; Wetzel, Gustav; Demircan, Ayhan; Lienau, Christoph; Giessen, Harald; Ivanov, Misha; Morgner, Uwe; et al.
Abstract: Recently, asymmetric plasmonic nanojunctions have shown promise as on‐chip electronic devices to convert femtosecond optical pulses to current bursts, with a bandwidth of multi‐terahertz scale, although yet at low temperatures and pressures. Such nanoscale devices are of great interest for novel ultrafast electronics and opto‐electronic applications. Here, the device is operated in air and at room temperature, revealing the mechanisms of photoemission from plasmonic nanojunctions, and the fundamental limitations on the speed of optical‐to‐electronic conversion. Inter‐cycle interference of coherent electronic wavepackets results in a complex energy electron distribution and birth of multiphoton effects. This energy structure, as well as reshaping of the wavepackets during their propagation from one tip to the other, determine the ultrafast dynamics of the current. It is shown that, up to some level of approximation, the electron flight time is well‐determined by the mean ponderomotive velocity in the driving field. Abstract : A novel class of nanojunctions are developed which demonstrate directed electron currents optically controllable at the time scale of tens and hundreds of femtoseconds, which work at room temperature and independently to the carrier‐envelope phase of the pump. We show the leading role of inter‐cycle quantum‐mechanical interference of the electronic wavepackets in the buildup of the current is shown.